2022
DOI: 10.1128/spectrum.03286-22
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Clostridium butyricum on Escherichia coli-Induced Endometritis in Mice via Ameliorating Endometrial Barrier and Inhibiting Inflammatory Response

Abstract: Endometritis is a common reproductive disease both in human and animals. It impairs female fertility by disrupting endometrial function. Antibiotics are widely used to treat endometritis in clinical practice, but the misuse of antibiotics often leads to antibiotic resistance. Therefore, there is an urgent need for new therapeutic agents to treat bacterial endometritis and overcome bacterial resistance. In this study, we found that C. butyricum could protect from E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Conversely, IL-10 serves as an anti-inflammatory regulator that not only inhibits the overexpression of proinflammatory factors, but also regulates intestinal homeostasis during immune defense processes ( Gao et al, 2012 ; Zigmond et al, 2014 ; Xu S. Q. et al, 2020 ). Generally speaking, CB primarily regulates the secretion of inflammatory cytokines through Toll-like receptor (TLR) pathways, such as TLR4/NF-κB pathway and TLR2/MyD88-independent pathway ( Hayashi et al, 2013 ; Wang et al, 2022 ).Then, we further uncovered the potential molecular pathways that contribute to anti-inflammatory properties of CBX 2021 through transcriptomics analysis. Interestingly, GSEA intuitively showed that CBX 2021 enhanced GPCR activity and its signaling pathway, while downregulating the Notch signaling pathway and the production of proinflammatory factors (IL-6 and TNF-α).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, IL-10 serves as an anti-inflammatory regulator that not only inhibits the overexpression of proinflammatory factors, but also regulates intestinal homeostasis during immune defense processes ( Gao et al, 2012 ; Zigmond et al, 2014 ; Xu S. Q. et al, 2020 ). Generally speaking, CB primarily regulates the secretion of inflammatory cytokines through Toll-like receptor (TLR) pathways, such as TLR4/NF-κB pathway and TLR2/MyD88-independent pathway ( Hayashi et al, 2013 ; Wang et al, 2022 ).Then, we further uncovered the potential molecular pathways that contribute to anti-inflammatory properties of CBX 2021 through transcriptomics analysis. Interestingly, GSEA intuitively showed that CBX 2021 enhanced GPCR activity and its signaling pathway, while downregulating the Notch signaling pathway and the production of proinflammatory factors (IL-6 and TNF-α).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lactococcus belongs to the Streptococcus family due to its production of bacteriocins and organic acids and has a number of beneficial functions [ 43 ]. An increase in the abundance of Clostridium populations has been related to a higher production of butyric acid [ 44 ], which can be absorbed and used as an energy source by colonic epithelial cells [ 45 ] and is able to modulate the immune system [ 46 ]. Parabacteroides is related to intestinal integrity disruption, with a higher abundance of Parabacteroides reflecting good intestinal barrier function [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these common probiotics, there is a need to explore novel probiotics targeting NDs. Clostridium butyricum is a notable probiotic that can ferment carbohydrates into butyric acid and has excellent protective effects against pathogenic microorganisms [ 130 ]. An animal study showed that a 4-week treatment with Clostridium butyricum (5 × 10 8 CFU/day) effectively protected against cognitive impairment and amyloid pathology by reducing microglia-mediated neuroinflammation in an AD (APP/PS1) mouse model [ 131 ].…”
Section: Potential Clinical Approaches Targeting the Microbiome In Ndsmentioning
confidence: 99%